IDENTIFIKASI JENIS GULMA PADA AREAL PERTANAMAN KELAPA DI DESA HATIVE BESAR - Vilma L Tanasale; Nureny Goo; Marlita H Makaruku; Anna Yuliana Wattimena (Pattimura Proceeding, 2022)
Coconut is one of the plantation crops that has decreased production in Ambon City. One of the causes of the decline in coconut production in every planting area in Ambon City is weeds. The decline in coconut production drastically from year to year in Hative Besar Village it is necessary to know the dominant weed types in the coconut plantation area in Hative Besar Village, Ambon City. The hypothesis proposed in this study is that there are dominant weeds in the coconut platation area. This study used the square method to collect data by direct observation in the fields 6 samples of weeds were taken from 6 samples of coconut plants. Qualitative and quantitative data were taken. The data needed ini this study consisted of primary data and secondary data. The dominant weed in the coconut plantation area in Hative Besar Village, Ambon City is the broad leaf weed Clidemia hirta